Isolated gastrocnemius tightness: impact on foot diseases - Moraes, Leonardo Vinícius de Matos; Borges, Vinícius Quadros; Ferraz, Gabriel Ferreira; Stéfani, Kelly Cristina (Scientific Journal of the Foot & Ankle, 2018)
Objective: To determine whether being overweight was associated with isolated gastrocnemius tightness (IGT), generating foot pain. Methods: This prospective cohort study evaluated 50 consecutively enrolled patients with a diagnosis of forefoot pain (e.g., metatarsalgia) or hindfoot pain (e.g., plantar fasciitis, insertional and noninsertional tendinopathy of the calcaneal tendon). Body mass index (BMI) and IGT (via the Silfverskiöld test) were evaluated. Gastrocnemius contracture was identified in cases with an ankle extension limitation of <10 degrees. Results: The mean age of the study patients was 64 years. The mean BMI was 27.8kg/m2. The most prevalent location of foot pain was the forefoot (66%), and 64% had IGT. However, IGT was not significantly correlated with BMI. Conclusion: Overweight patients showed an IGT prevalence of 66%. However, there was no correlation between BMI and the presence of IGT. Level of Evidence II; Diagnostic Studies.